The adoption of electric vehicle in Thailand with the moderating role of charging infrastructure: an extension of a UTAUT - Sheraz Ahmad; Singha Chaveeesuk; Wornchanok Chaiyasoonthorn (My University, 2024)
Electric vehicles (EVs) have the potential to greatly reduce the amount of gasoline consumed and carbon emissions produced during transportation. Consequently, the Thai government actively advocates for the widespread use of electric vehicles (EVs). This study has examined the factors that influence the adoption of electric vehicles in Thailand, with the moderation of charging infrastructure. The research builds upon the UTAUT2 model and incorporates new elements such as environmental concerns, satisfaction with incentive policies, trust, and the availability of charging infrastructure. Environmental concerns, price value, and hedonic motivation significantly affect use behaviour through trust and behaviour intentions; however, facilitating conditions do not affect them. Habits positively affect use behaviour through behaviour intention, though factors such as effort expectancy and social influence satisfaction with policies showed insignificant results when affecting use behaviour. The moderating effect of charging infrastructure showed an insignificant result.
Keywords: Electric Vehicles and Infrastructure